SARS-CoV-2 Seroprevalence Following a Large-Scale Vaccination Campaign in Portugal: Results of the National Serological Survey, September - November 2021 - Kislaya, Irina (2022)
Introduction: Following a COVID-19 mass vaccination campaign, it is important to evaluate the population level of SARS-CoV-2 antibodies. The aim of this study was to estimate the seroprevalence rate of SARS-CoV-2 specific antibodies acquired due to infection or vaccination in the Portuguese population.Material and Methods: The National Serological Survey (third wave – ISN3COVID-19) is a cross-sectional nationwide epidemiological study developed on a sample of 4545 Portuguese residents aged one year or older, between the 28th September 2021 and the 19th November 2021. The SARS-CoV-2 anti-nucleoprotein and anti-spike IgG antibody levels were determined in serum samples using Abbott Chemiluminescent Microparticle Immunoassays. Seroprevalence estimates were stratified by age group, sex, administrative region and self-reported chronic conditions. Medians and respective 95% confidence intervals were used to describe the distribution of SARS-CoV-2 specific antibodies in specific population subgroups.Results: The total seroprevalence rate of SARS-CoV-2 was 86.4% (95% CI: 85.2% to 87.6%). A higher seroprevalence rate was estimated for women (88.3%), 50 to 59 years-old (96.5%) and in those with two or more self-reported chronic conditions (90.8%). A higher IgG (anti-Spike) concentration was observed in individuals vaccinated with the booster dose (median = 1 2601.3 AU/mL; 95% CI: 4127.5 to 19 089.1).Conclusion: There was a significant increase in SARS-CoV-2 seroprevalence following the mass vaccination campaign in Portugal. It is important to continue to monitor the distribution of specific SARS-COV-2 antibody at the population level to further inform public health policies.